Oxidative stress-mediated particulate matter affects the risk of relapse in schizophrenia patients: Air purification intervention-based panel study. (1st January 2022) - Wei, Qiannan; Ji, Yifu; Gao, Hua; Yi, Weizhuo; Pan, Rubing; Cheng, Jian; He, Yangyang; Tang, Chao; Liu, Xiangguo; Song, Shasha; Song, Jian; Su, Hong
Abstract: Particulate matter (PM) exposure increased the risk of hospital admission and was related to symptoms of schizophrenia (SCZ). However, there are limited studies on the relationship between PM exposure and SCZ relapse risk, and the underlying biological mechanisms remain unclear. We designed an air purification intervention study under a 16-day real air purifier scenario and another 16-day sham air purifier scenario, with a 2-day washout period. Twenty-four chronic stable male patients were recruited. The oxidative stress biomarkers were measured including serum catalase (CAT), superoxide dismutase (SOD), total antioxidant capacity (T-AOC), malondialdehyde (MDA), and nitric oxide (NO). The relapse risk was evaluated by the early signs scale (ESS). Linear mixed effect models were fitted to establish the associations between PM exposure and ESS and oxidative stress. Mediation model was performed to explore the mediation effect of oxidative stress on the PM-ESS association. Higher concentrations of PM2.5 /PM10 exposure were associated with an elevated risk of relapse of SCZ . For each 10 μg/m 3 in PM2.5 concentration, the scores of ESS and subscales of incipient psychosis (ESS-IP), depression/withdrawal (ESS-N), anxiety/agitation (ESS-A), and excitability/disinhibition (ESS-D) were increased by 4.112 (95% CI: 3.174, 5.050), 1.516 (95%CI: 1.178, 1.853), 1.143 (95%CI: 0.598, 1.689), 1.176 (95%CI: 0.727, 1.625) and 0.238 (95%CI: 0.013, 0.464), while logCAT, SOD and T-AOC were reduced by 0.039 U/ml (95% CI: 0.017, 0.060), 1.258 U/ml (95% CI: 0.541, 1.975), and 0.076 mmol/l (95% CI: 0.026, 0.126). In addition, pathways of "PM2.5 →T-AOC→ESS-A″ and "PM2.5 →T-AOC→ESS-D″ were found, with significant T-AOC mediated effects 15.70% ( P  = 0.02) and 52.99% ( P  = 0.04). Our findings suggest that PM may increase the risk of anxiety, depression, excitability, and incipient psychosis behaviors in SCZ patients, while reducing the function of the antioxidant system. The decrease of T-AOC may medicate the PM-ESS association in SCZ. Graphical abstract: Image 1 Highlights: Higher levels of PM2.5 /PM10 exposure were related with elevated risk of relapse of schizophrenia. Exposure to PM2.5 /PM10 decrease the function of antioxidant system especially the level of T-AOC. T-AOC decrease might play the mediated role on the PM-schizophrenia relapse risk association.